THE ALPHABET AND SYLLABLE METHOD AS A TEACHER STRATEGY IN IMPROVING BEGINNING READING IN PHASE A CLASS I STUDENTS AT SEKOLAH DASAR NEGERI KALIPUCANG KULON BATANG - Artiningsih, Fauziah; Mukhlis, Abdul; Widodo, Dhanu Priyo (Journal of Educational Review and Research, 2023)
A teacher is someone who plays an important role in education and tries various ways to overcome the difficulties experienced by students. One of the learning difficulties experienced by students, especially phase A, is difficulty in initial reading. If initial reading difficulties can be overcome well, it will be easy for students to take the next stage of reading. This research aims to describe the alphabet method as a teacher's strategy in improving initial reading skills in phase A class I students at the Kalipucang Kulon State Elementary School, to outline the teacher's strategy in improving initial reading skills using the syllabic method for phase A class I students in elementary school. Kalipucang Kulon State, and to explain the factors that influence initial reading difficulties in phase A class I students at Kalipucang Kulon State Elementary School. The type of this research is field research, namely research carried out directly to obtain data with a qualitative approach namely the approach used to gather information from reasonable conditions. Meanwhile, the data sources used are primary data sources and secondary data sources. Meanwhile, the data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data condensation, data display, and conclusion drawing. The results of this research show that: (1) The alphabet method as a teacher's strategy in improving initial reading skills in phase A class I students at Kalipucang Kulon Batang State Elementary School, is considered quite successful in improving initial reading skills, there are changes in the students. (2) The teacher's strategy in improving initial reading skills using the syllabic method for phase A class I students at the Kalipucang Kulon Batang State Elementary School has not yet been achieved optimally, but little by little there has been an improvement in the students' reading skills. (3) The factors that influence initial reading difficulties in phase A class I students at Kalipucang Kulon Batang State Elementary School are caused by four factors, namely physiological factors, intellectual factors, environmental factors and psychological factors.